PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA PINTAR (ULTAR) BERBANTUAN FLASHCARD PADA MATERI ENERGI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SEKOLAH DASAR - Devi Vitria Wahyu Mela Ayunda; Sri Cacik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem raised in this study is the low learning outcomes of grade VI students in IPAS subjects, especially energy material, which is caused by the lack of use of innovative and fun learning media. The media used are still conventional and have not been adapted to the characteristics of elementary school students who are at the concrete operational stage according to Piaget's theory. The purpose of this research is to develop innovative learning media in the form of Ular Tangga Pintar (ULTAR) assisted by Flashcards to improve the learning outcomes of grade VI elementary school students on energy material. This research uses the Research and Development (R&D) method with the ADDIE development model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were students of class VI UPT SD Negeri Gemulung 3, with a total of 7 students. Data collection techniques were carried out through observation, interviews, questionnaires, documentation, as well as pretests and posttests. The data obtained were analyzed using validation test, practicality analysis, and effectiveness test with N-Gain formula. The results showed that ULTAR media assisted by flashcards was declared very valid by linguists (96%), material experts (98%), and media experts (98%). In terms of practicality, the results were very practical based on teacher questionnaires (100%) and student questionnaires (98.2%). This media also proved to be very effective in improving learning outcomes with an average N-Gain of 0.96. Thus, this media is suitable to be used as an alternative to fun and effective thematic learning in elementary schools.